Diagnostic Value of microRNA for Alzheimer’s Disease: A Systematic Review and Meta-Analysis - Hu, Yong-Bo; Li, Chun-Bo; Song, Ning; Zou, Yang; Chen, Sheng-Di; Ren, Ru-Jing; Wang, Gang (Frontiers in Aging Neuroscience, 2016)
Sound evidence indicates that micro-RNA s (miRNAs) are aberrantly expressed in Alzheimer's disease (AD) patients. We performed a systematic review and meta-analysis investigating the role of miRNA in AD pathogenesis and their clinical diagnostic value, a systematic review of literature and meta-analysis of clinical trials were performed. In the systematic review, 236 papers were included and we reviewed the dysregulated miRNA expression in different parts of AD patients in order to identify the relationship between aberrantly expressed miRNAs and AD pathology. In the subsequent meta-analysis, seven studies were statistically analyzed with the following results: pooled sensitivity 0.86 (95%CI 0.79-0.90), pooled specificity 0.87 (95%CI 0.72-0.95), diagnostic odds ratio 28.29 and the area under the curve 0.87. In conclusion, our review indicated that aberrant expression of various miRNAs play an important role in the pathological process of AD, and statistical analysis of quantitative studies reveal the potential value of specific miRNAs in the diagnosis of AD.